2014
DOI: 10.1021/cm502816a
|View full text |Cite
|
Sign up to set email alerts
|

Ordered Heterostructures of Two Strictly Alternating Types of Nanoreactors

Abstract: One-dimensional crystalline heterostructures of two types of nanoreactors strictly alternating along the stacking direction are obtained by partial ion exchange into a synthetic clay mineral distinguished by an outstandingly homogeneous charge density. The driving force for the formation of these high interface architectures is proven to be founded in densely packed cationic molecules in the interlayer with a charge density deviating from the charge density of the host clay mineral. The established mechanism r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
37
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 40 publications
2
37
0
4
Order By: Relevance
“…[8] Surprisingly,wenow find that immersing the microcrystalline powder of the ordered interstratified heterostructure into deionized water results in the material swelling ( Figure 1) into ay ellow gel with ah igh viscosity.Aconcomitant huge increase in sample volume ( Figure S1) is observed, which indicates adelamination of the one-dimensional crystals into thinner nanoplatelets.S table suspensions are formed at higher dilution, and a" Schlieren" texture implies ah igh stability of the suspension in water ( Figure S2). In the mixture used here,t he swelling of the Na + interlayers is restricted to the two-layer hydrate and no exfoliation is observed at the stage where the heterostructure is formed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[8] Surprisingly,wenow find that immersing the microcrystalline powder of the ordered interstratified heterostructure into deionized water results in the material swelling ( Figure 1) into ay ellow gel with ah igh viscosity.Aconcomitant huge increase in sample volume ( Figure S1) is observed, which indicates adelamination of the one-dimensional crystals into thinner nanoplatelets.S table suspensions are formed at higher dilution, and a" Schlieren" texture implies ah igh stability of the suspension in water ( Figure S2). In the mixture used here,t he swelling of the Na + interlayers is restricted to the two-layer hydrate and no exfoliation is observed at the stage where the heterostructure is formed.…”
mentioning
confidence: 99%
“…[2] Al ayered host may offer the additional advantage of pronounced inherent structural anisotropy.Consequently,the interlayer structure formed by the intercalation of organic compounds between asandwich of two layers ensures awelldefined orientation in the confined space. [8] Surprisingly, we now succeeded in spontaneously delaminating this material into double stacks of two highly transparent, flexible silicate layers that encapsulate ac entral organic layer of oriented functional molecules.M oreover,t he large aspect ratio of these delaminated double stacks inevitably leads to perfectly textured films upon casting suspensions on flat substrates,which in turn results in apseudoepitaxial orientation of the encapsulated functional moiety. [5,6] In this regard, Kunz et al have shown that the intercalation of [Ru(bpy) 3 ] 2+ (bpy = 2,2'-bipyridine) into as ynthetic clay mineral leads to the polarized emission of light.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[19,20] In our case,the NH 4 + interlayers are significantly above while the Na + interlayers are below the charge density of the host layers (Supporting Information, Figure S1). [19,20] In our case,the NH 4 + interlayers are significantly above while the Na + interlayers are below the charge density of the host layers (Supporting Information, Figure S1).…”
mentioning
confidence: 61%
“…[17][18][19] We recently established ag eneral synthesis for such crystalline heterostructures composed of synthetic layered silicates (Figure 1a). [19,20] Herein, we prepare ordered heterostructures of layered silicates where interlayers with different reactivities strictly alternate in stacks.Such heterostructures offer predetermined slippage planes that provide ap recise,s calable,a nd quantitative preparation route for desired bilayer materials. [5,21] The + interlayers (yellow) and hydrated Na + interlayers (blue) induces highly selectivee xfoliation into bilayers (b).…”
mentioning
confidence: 99%